A mechanistic roadmap for the clinical application of cardiac cell therapies. (June 2018) - Marbán, Eduardo
Abstract The development of cells for regenerative therapy has encountered many pitfalls on its path to clinical translation. In cardiology, clinical studies of heart-targeted cell therapies began two decades ago, yet progress towards reaching an approved product has been slow. In this Perspective, I provide an overview of recent cardiac cell therapies, with a focus on the hurdles limiting the translation of cell products from research laboratories to clinical practice. By focusing on heart failure as a target indication, I argue that strategies for overcoming limitations in clinical translation require an increasing emphasis on mechanism-supported efficacy, rather than on phenomenological observations. As research progresses from cells to paracrine mechanisms to defined factors, identifying those defined factors that are involved in achieving superior therapeutic efficacy will better inform the use of cells as therapeutic candidates. The next generation of cell-free biologics may provide the benefits of cell therapy without the intrinsic limitations of whole-cell products. This Perspective provides an overview of recent cardiac cell therapies and their limitations, and argues for the need of deeper mechanistic understanding that informs the use of cells and of next-generation cell-free biologics in cardiac regeneration.